Muscle Dysmorphia in Fitness Center Members: Its Affecting Factors and Impacts - Fitranti, Deny Yudi; Widyastuti, Nurmasari; Noer, Etika Ratna; Rahadiyanti, Ayu; Dieny, Fillah Fithra; Purwanti, Rachma; Sandi, Dewi Kurnia; Destikasari, Widya (Kesmas, 2022)
Muscle dysmorphia (MD) has several impacts on the decline in social and health functions. This study aimed to determine the correlation between MD with eating behaviors and exercise loading among fitness center members and analyze the factors affecting it. This study used a cross-sectional design with 100 subjects chosen by a consecutive sampling method at three fitness centers in Semarang City. The subjects were all male members of an active fitness center between 17 and 45 years. The data of MD were obtained using the Drive Muscular Scale (DMS), while eating behavior data were obtained using the Eating Attitude Test-40 (EAT-40) and the training load data, including the duration and frequency of weight training data. Social influence data, self-esteem data, and perfectionism data were obtained using a questionnaire. The findings revealed that 61% of the subjects experienced MD, 80% experienced impaired eating behavior, and 80% consumed supplements. There was a correlation between the occurrence of MD with eating behavior with PR = 2.56 and consumption of supplements with PR = 2.56. The most influential factor on MD was a social influence.